INTEGRASI NILAI KOLABORATIF DAN STRATEGI DALAM PEMBELAJARAN MATEMATIKA MELALUI GAME BANTENG PERTAHANAN DI TAMAN ALAM OLEAN - Nur Hasanah ana (LPPM Universitas Abdurrab, 2025)
Mathematics is often considered a complicated and boring subject, especially in mathematical logic. The purpose of this study is to integrate collaborative and strategic values ​​into mathematics learning through the traditional game